Towards zero-waste buildings - Building design for reuse and disassembly - Grmela, Václav (My University, 2020)
This master thesis investigates the potentials of zero- waste buildings as one of the strategies to be used in the sustainable building environment. According to the EU Waste Framework directive, 70% of all construction and demolition waste has to be reused or recycled, by 2020. The goal of this study is to bring up some of the design challenges connected to this and increase interest for a sustainable praxis. Participation in various events, meetings and visiting exhibitions, further helped to gain a comprehensive understanding of the topic. Some of the involved actors, such as architects, engineers and several product companies, were contacted, to get a holistic view of state of the art in the field. Based on the investigation, a series of possible design solutions is presented in the catalogue that forms the central part of the thesis booklet. This part has the goal to give the reader an idea of how does design for disassembly might look like and inspire to carry out further investigations. An analysis of various projects and the methods, used during the construction and dismantling of the buildings, show that there is a big potential for improvement. Building and component design that prevents a product’s effective dismantling needs to be reviewed. Not producing more waste, ensuring the value preservation and simple reuse in future, shall be considered a priority.